Religion and Satisfaction with Life in Polish Seniors: Mediation by Forgiveness and Hope - Rydz, Elżbieta; Tychmanowicz, Anna; Zarzycka, Beata 1974- (2024)
This study examined the mediating role of forgiveness and hope in the relationship between religiousness and satisfaction with life in late adults in Poland. Participants were 237 people (165 females and 72 males) aged between 60 and 92. The mean age of the sample was 68.37 years (SD = 6.92), and the most represented religious affiliation was Roman Catholic (98.3%). Satisfaction with life is related to the centrality of religiousness. In the surveyed seniors, hope and tendency to forgive mediated the relationship between the centrality of religiousness and satisfaction with life.
Keywords: Forgiveness; Hope; Polish seniors; Religiousness; Satisfaction with life